Comparison of visual function analysis of people with low vision using three different models of augmented reality devices - Sarika Gopalakrishnan; Arathy Kartha; Ronald Schuchard; Donald Fletcher (PLoS ONE, 2025)
We compared visual function in individuals with low vision (>20/60) using three different models of augmented reality (AR) devices: Ziru, IrisVision, and NuEyes-Pro3. The distance visual acuity (VA) was measured in high luminance high contrast (HLHC), high luminance low contrast (HLLC), low luminance high contrast (LLHC), and low luminance low contrast (LLLC) settings. The other tests were near VA, distance and near contrast sensitivity (CS), color vision, depth perception and indoor navigation. The change in visual function without and with AR devices was analyzed. Out of 27 participants, 17 were female. The mean age was 66.7 ± 18.2 years. The median baseline VA was 0.66 (0.79) logMAR in HLHC, 0.87 (0.54) logMAR in HLLC, 0.84 (0.67) logMAR in LLHC and 1.04 (0.34) logMAR in LLLC. The median baseline near VA was 0.55(0.4) logMAR, distance and near CS was 1.10(0.26) logCS, and 1.20(0.30) logCS respectively. Distance and near vision showed significant differences with both Ziru and IrisVision (p < 0.01), but not with NuEyes. There was a significant change in CS using Ziru and IrisVision for both distance and near (p < 0.05) but both reduced significantly with NuEyes (p < 0.01). During the objective identification task on the indoor environment using AR devices, head-level objects were missed more compared to waist or floor-level objects across all three models. Majority of the visual functions improved with Ziru and IrisVision, with limited improvement in certain lighting condition of distance visual acuity with NuEyes.